1994
DOI: 10.1002/chin.199447217
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Aborycin ‐ A Tricyclic 21‐Peptide Antibiotic Isolated from Streptomyces griseoflavus.

Abstract: The screening for growth inhibitors against Bacillus subtilis revealed a peptide antibiotic produced by Streptomyces griseoflavus TU 4072. Very high yields of the antibiotic named aborycin were obtained by cultivation in a medium containing soybean meal and sucrose. Isolation from the mycelium was carried out by a combination of extraction and gel chromatography. Preparative HPLC yielded the uniform antibiotic. The structure elucidation was based on GC amino acid analysis on a chiral phase, automated Edman deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 1 publication
2
29
0
Order By: Relevance
“…34 Supplementary Table S1). [1][2][3][4][5][6][7][8][9][10][11][12][13][14]16,17,19,20,32,33 In general, all so far known lasso peptides originated from either proteobacterial or actinobacterial sources (Figure 4), even though genome mining approaches have revealed putative biosynthetic gene clusters in other phyla as well. 21,26−28 The biological activities hitherto identified for lasso peptides encompass a wide variety of functions ( Figure 2).…”
Section: Discovery Biological Activities and Biosynthesismentioning
confidence: 97%
“…34 Supplementary Table S1). [1][2][3][4][5][6][7][8][9][10][11][12][13][14]16,17,19,20,32,33 In general, all so far known lasso peptides originated from either proteobacterial or actinobacterial sources (Figure 4), even though genome mining approaches have revealed putative biosynthetic gene clusters in other phyla as well. 21,26−28 The biological activities hitherto identified for lasso peptides encompass a wide variety of functions ( Figure 2).…”
Section: Discovery Biological Activities and Biosynthesismentioning
confidence: 97%
“…Lasso peptide production has been mainly associated with members of the phyla Actinobacteria and Proteobacteria and the best-studied molecules of this family are produced by representative species within these phyla ( Weber et al, 1991 ; Salomon and Farías, 1992 ; Helynck et al, 1993 ; Potterat et al, 1994 ; Tsunakawa et al, 1995 ; Kimura et al, 1997 ; Knappe et al, 2008 ; Hegemann et al, 2013a ). Moreover, genome-guided studies focused on natural product discovery often point to these bacterial phyla as promising sources of lasso peptides ( Severinov et al, 2007 ; Hegemann et al, 2013b ; Maksimov and Link, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lasso peptides produced by actinobacteria are generally active against Gram-positive bacteria, while those produced by proteobacteria show a narrow spectrum of activity directed against bacteria closely related to the producing strain. Propeptin and aborycin constitute exceptions to this trend, being active on both Gram-positive and Gram-negative bacteria such as Pseudomonas (Potterat et al 1994;Kimura et al 1997a). Antimicrobial assays showed that propeptin (Kimura et al 1997a), capistruin ) and astexin-1 have only a weak activity and no significant activity is noticed for anantin (Weber et al 1991), sungsanpin (Um et al 2013), caulosegnins ) and xanthomonins ).…”
Section: Antimicrobialsmentioning
confidence: 99%